ANALISIS PROFIL PROTEIN PADA TELUR PUYUH DENGAN PERENDAMAN LARUTAN KAPUR TERHADAP VARIASI LAMA PENYIMPANAN BERBASIS SDS-PAGE: PROTEIN PROFILE ANALYSIS OF QUAIL EGGS SOAKED IN LIME SOLUTION AGAINST STORAGE DURATION VARIATIONS BASED ON SDS-PAGE - Nanda Yaultsa; Meutia Srikandi Fitria; Aditya Rahman Ernanto (Jurnal Kajian Ilmiah Kesehatan dan Teknologi, 2025)
Quail eggs are a source of protein that many people consume. Eggs have a short shelf life. The longer eggs are stored, the quality and freshness of eggs decreases. In order to extend the shelf life of eggs, they are treated with a lime solution. The pupose of this study was to determine the protein profil of quail eggs by immersing in lime solution on variations in storagetime based on SDS-PAGE. The results showed that the highest bands were in samples T3 (B), T4 (A and B), T1 (A and B), T2 (A and B) respectively, namely 3 major bands and 6 minor bands, 9 minor bands, 1 major band and 8 minor bands, 3 major bands and 5 minor bands, 2 major bands and 6 minor bands, 3 major bands and 5 minor bands, 1 major band and 7 minor bands. While the lowest band results are in sample T3 (A), namely 1 major band and 6 minor bands. Based on these results, it can be concluded that there are differences in the protein profile of quail eggs between the control sample and the treated sample.